Depletion of serotonin relieves concanavalin A-induced liver fibrosis in mice by inhibiting inflammation, oxidative stress, and TGF-β1/Smads signaling pathway. (1st April 2021) - Pang, Qing; Jin, Hao; Wang, Yong; Dai, Mengnan; Liu, Shuangchi; Tan, Yi; Liu, Huichun; Lu, Zheng
Highlights: Serotonin depletion improved liver damage in LF mice. Serotonin depletion inhibited collagen deposition in LF mice. Serotonin depletion reduced serum and intrahepatic inflammatory cytokines in LF mice. Serotonin depletion mitigated oxidative stress in liver tissues in LF mice. Serotonin depletion inhabited TGF-β1/Smads signaling pathway in LF mice. Abstract: Serotonin exerts important functions in several liver pathophysiological processes. In this study, we investigated the role of serotonin in concanavalin A (Con A)-induced liver fibrosis (LF) in mice and the underlying mechanisms. To establish the mouse model of LF, mice of wild-type (WT) and tryptophan hydroxylase 1 ( Tph1 ) knockout (serotonin depletion) received Con A for 8 successive weeks. Degree of fibrosis was assessed by Sirius red staining, as well as the measurements of alpha smooth muscle actin (α- SMA), hydroxyproline (Hyp) and type I collagen in liver tissues. To elucidate the potential mechanisms, we assessed the effect of serotonin depletion on inflammatory, oxidative stress as well as TGF-β1/Smads signaling pathway. We found that serotonin depletion significantly inhibited collagen deposition as evaluated by less collagenous fiber in Sirus Red staining and reduced contents of Hyp and type I collagen. In addition, the absence of serotonin significantly inhibited the release of several inflammatory cytokines, including interleukin-6 (IL-6), interferon-gamma (IFN-γ), tumor necrosis-alpha (TNF-α), and transforming growth factor β1 (TGF-β1). Oxidative stress was also largely mitigated in LF mice with serotonin deficiency as manifested by the decreases of oxidative stress markers (malonaldehyde (MDA) and myeloperoxidase (MPO)), as well as the increases of antioxidant stress indicators (glutathione (GSH), and GSH-px, catalase (CAT), superoxide dismutase (SOD)) in liver tissues. Moreover, the lack of serotonin may provide an antifibrotic role by inhibiting the intrahepatic expressions of TGF-β1, phosphorylated-smad2 (p-smad2), and phosphorylated-smad3 (p-smad3). These results indicated that, serotonin depletion attenuates Con A-induced LF through the regulation of inflammatory response, oxidative stress injury, and TGF-β1/Smads signaling pathway.